The Role of Local Governments in Environmental Globalization - Takao, Yasuo (Amsterdam University Press, 2025)
The global environmental challenges suggest that a new approach needs to be taken to address a cross-scale and multi-level issue of environmental risk reduction. Environmental problems stretch across scales of geographic space and require action at multiple levels of jurisdictions. But the suggested approaches face difficulties in policy coordination created by the plurality of stakeholders and also attended with organizational complexity. In this context much of the scholarly work to date tends to overlook the role of sub-national governments. Sub-national governments occupy a strategic position to act as intermediate agents to reconnect local action with national policy and turn global strategies into local action for problem-solving. The author argues that policy coordination and leadership is much easier where there are environmental benefit-recipients with real needs at the local level. This chapter sets out to examine how such a framework might be identified to support the future shape of Japan’s environmental policy and governance.